Tinjauan Konstitusional Penunjukan Penjabat Kepala Daerah Berdasarkan Prinsip Demokrasi dan Kedaulatan Rakyat: Penelitian - Putri Zein Handayani; Ernawati (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The principle of popular sovereignty as enshrined in Article 1 paragraph (2) and Article 18 paragraph (4) of the 1945 Constitution of the Republic of Indonesia mandates that regional head positions must be filled democratically. However, the 2024 simultaneous regional election policy resulted in leadership vacancies across 271 regions, which were subsequently filled through an appointment mechanism under the Minister of Home Affairs Regulation Number 4 of 2023. This research aims to analyze the conflict between the necessity of filling administrative vacancies and democratic ideals, while critically examining central government dominance within the process. The research method employed is normative legal research with statutory and conceptual approaches conducted through literature review. The results indicate that the direct appointment mechanism by the President and the Minister of Home Affairs has effectively amputated the people's right to sovereignty in the regions. The role of the Regional House of Representatives (DPRD) has been reduced to a mere administrative formality, leading to a deficit in moral legitimacy and a shift in accountability from horizontal (to the local community) to vertical (to central authorities). This top-down and closed appointment process has proven to trigger public resistance, as evidenced by cases in Jayapura Regency and Morotai Island. In conclusion, a regulatory reconstruction prioritizing the principle of meaningful participation is essential to ensure that the governmental transition remains rooted in the spirit of popular sovereignty and constitutional regional autonomy.